The Relationships Between Teacher Self-efficacy, Perceived Collective Efficacy and Burnout - Čeponienė, Daiva; Lazauskaitė-Zabielskė, Jurgita (Acta Paedagogica Vilnensia, 2017)
Burnout is defined as a state of physical, emotional and mental exhaustion, resulting from long-term involvement in work situations that are emotionally demanding (Schaufeli, Greenglass 2001). Researchers admit that certain professional groups, including teachers (e. g., Antoniou et al. 2006), are at a greater risk of suffering burnout. Given the detrimental effects of burnout for an individual’s health, wellbeing and performance, scientific research has been aimed to explore the factors contributing to burnout. Some studies suggest (e. g., Skaalvik, Skaalvik 2007) that high levels of self-efficacy may reduce burnout. Moreover, as teachers usually work in teams, the beliefs about the ability of the team of teachers to attain teaching goals may also contribute to diminishing burnout (Goddard et al. 2004). However, such studies are very scarce. Therefore, the study was conducted with the aim to establish the relationship between individual self-efficacy, perceived collective efficacy, strain factors and burnout among educational staff. 130 teachers from the district and city of Pasvalys were surveyed. The results of the study showed that the level of work-related and personal burnout in teachers was not related to demographic variables such as age, education, tenure and qualification. Moreover, strain factors were found to predict burnout. More precisely, communication with conflictive parents of the students was related to workrelated burnout, while the quality of the relationship with a supervisor was related to personal burnout. Furthermore, the results of the study revealed that teacher self-efficacy, in terms of the perceived ability to keep discipline in the classroom, was related to lower levels of work-related burnout. However, teacher self-efficacy, in terms of the perceived ability to cope with changes and challenges in teaching, predicted higher work-related burnout. In addition, burnout was not related to the perceived ability to motivate students and to cooperate with colleagues and parents. Finally, the perceived teacher collective efficacy did not predict personal and work-related burnout.